2006
DOI: 10.1021/jf062613m
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Geographic Origin of Onions between Three Main Production Areas in Japan and Other Countries by Mineral Composition

Abstract: Onions (Allium cepa L.) are produced in many countries and are one of the most popular vegetables in the world, thus leading to an enormous amount of international trade. It is currently important that a scientific technique be developed for determining geographic origin as a means to detect fraudulent labeling. We have therefore developed a technique based on mineral analysis and linear discriminant analysis (LDA). The onion samples used in this study were from Hokkaido, Hyogo, and Saga, which are the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 15 publications
11
42
1
Order By: Relevance
“…This could be explained by a higher concentration of these elements in the smaller achenes characteristic of this cultivar. In general, the trend observed in studies on other plant species (Ariyama et al, 2007;Manzelli et al, 2010) was confirmed, indicating a higher influence of the environment, with respect to genotype, on the mineral content.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This could be explained by a higher concentration of these elements in the smaller achenes characteristic of this cultivar. In general, the trend observed in studies on other plant species (Ariyama et al, 2007;Manzelli et al, 2010) was confirmed, indicating a higher influence of the environment, with respect to genotype, on the mineral content.…”
Section: Discussionsupporting
confidence: 55%
“…Ash content [% dry matter (DM)] was determined in three replicates for each sample after incineration in a muffle furnace at 550°C, according to the official (Padín et al, 2001;Ariyama et al, 2007;Di Giacomo et al, 2007). Flour samples were digested with HNO3 [0.5 g in 10 mL of 7:3 (v/v) ultra-pure HNO3/Milli-Q H2O] in a microwave accelerated reaction system (Model MARS 6; CEM Corp., Matthews, NC, USA).…”
Section: Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with past studies [49][50][51], the use of multielemental analysis required accurate statistical data treatment. Initially, three main groups were defined by means of an agglomerative hierarchical cluster (AHC).…”
Section: Paprikamentioning
confidence: 66%
“…These slurry samples were properly diluted in 5% V/V HNO 3 to aid the analyte extraction to the aqueous phase, to carry out the determination of copper and zinc by flame atomic absorption spectrometry, following a procedure reported by Marco et al, 2003. 1.2 Determination of calcium, potassium, manganese, iron, copper and zinc levels in representative samples of two onion cultivars by flame atomic absorption spectrometry using ultrasonic assisted leaching The onion is one of the most important cultivars in the world. The determination of major, minor and trace element levels is an important tool for the enhancement of production efficiency in the field of agriculture, provenance, and contamination risk evaluation (Ariyama et al, 2007;Abdullahi et al, 2008;Abdullahi et al, 2009). There is a necessity for new analysis methods and simple sample preparation procedures.…”
Section: Determination Of Zn and Cu In Crude Human Brain Slurry Samplmentioning
confidence: 99%